ความเครียดและการจัดการความเครียดของนักศึกษาพยาบาล ขณะฝึกปฏิบัติงานห้องคลอด - เลิศสาครศิริ มาลีวัล (วารสารพยาบาลเกื้อการุณย์, 2016)
การจัดการเรียนการสอนทางพยาบาลศาสตร์มีทั้งภาคทฤษฏีและภาคปฏิบัติ ซึ่งการฝึกปฏิบัติทำให้นักศึกษามีความเครียดและวิตกกังวลสูงกว่าการเรียนภาคทฤษฎีในชั้นเรียน โดยเฉพาะอย่างยิ่งการปฏิบัติงานห้องคลอด นักศึกษาจะมีความเครียดซึ่งเป็นความรู้สึกตื่นเต้น วิตกกังวล และกลัวความล้มเหลว โดยจะส่งผลต่อการเรียนรู้และความมั่นใจของนักศึกษาสาเหตุที่ก่อให้เกิดความเครียดในการปฏิบัติงานจะเกี่ยวข้องกับงานที่ได้รับมอบหมาย ความคาดหวัง สัมพันธภาพกับอาจารย์ บุคลากร เพื่อน ลักษณะอุปนิสัยส่วนบุคคล สิ่งแวดล้อม และการประเมิน ผลการปฏิบัติงาน ซึ่งระดับความรุนแรงของความเครียดที่เกิดขึ้นในแต่ละบุคคลจะไม่เท่ากัน ขึ้นอยู่กับการยอมรับและความสามารถในการปรับตัวของแต่ละบุคคลต่อความเครียดที่เกิดขึ้นกระบวนการจัดการความเครียดประกอบด้วย สิ่งที่ทำให้เกิดความเครียด การประเมินปัญหา และการเผชิญความเครียดแบบมุ่งแก้ปัญหา หรือการลดอารมณ์ตึงเครียด จะเปลี่ยนไปตาม สถานการณ์และการประเมินของนักศึกษาแต่ละคนแนวทางปฏิบัติของนักศึกษาพยาบาลเพื่อช่วยคลายความเครียด สามารถทำได้ดังนี้ คือ การออกกำลังกาย การพักผ่อน การพูดอย่างสร้างสรรค์ การสร้างสัมพันธภาพที่ดีกับเพื่อนร่วมงาน การแก้ปัญหาอย่างถูกวิธี การปรับเปลี่ยนความคิด การสร้างความเข้มแข็งทางจิตใจ และการรู้จักยืนยันสิทธิของตน The Stress, Stress Management of Nursing Students during Practice in the Labor Room Teaching and learning in nursing are both theoretical and practical. Practice in the labor room in particular causes students to have more stress and anxiety than learning theory in the classroom. Students will have a sense of excitement, stress, anxiety and fear of failure. It will affect student learning and confidence. The causes of stress are related to the work that has been assigned by, the expectations, and the relationships with faculty, staff, friends, personal characteristics, environmental characteristics and evaluation of performance during practice. The individual severity of the stress is not equal, based on the individual ability to accept and adapt to stress. The process of stress management includes events or stressors, appraisal, and problem-focused coping or emotional-focused coping. It will change depending on the situation and the assessment of each student.The guideline of stress reduction for nursing students compose of exercise, rest, creatively speaking, building good relationships with colleagues, proper problem solving, changing ideas, strengthening mental acceptance and asserting their rights.